Adults’ and children’s reasoning about the potential of diverse groups - Weatherhead, Drew; Nancekivell, Shaylene E.; Workye, Rebeka (Frontiers in Psychology, 2024)
Introduction In two experiments, we examine the degree to which adults (Experiment 1) and children 5-to-8-years-old (Experiment 2) use diversity to infer a group’s cooperative and innovative potential. Methods Participants heard a child-friendly vignette about a competition in which a homogenous and diverse group were competing to design the perfect toy. They were then probed using questions related to the group’s innovative potential and cooperative potential and asked to justify their responses. Results Results show that adults believed that the diverse group would produce the more innovative product, while children endorsed the homogenous group. When asked a question probing cooperation, adults selected the homogenous group, whereas children were equally likely to select either group. Analysis of adults’ explanations showed their explanations differed depending on which group they endorsed. However, children’s explanations did not show this nuance. Exploratory analyses suggest that participants’ responses were influenced by their personal experiences with gender and racial diversity. Discussion People’s appreciation of the link between group diversity and group potential changes across the lifespan likely due to life experiences.